EFFECT OF BREAST CARE ON COLOSTRUM EXPENDITURE IN PREGNANT MOTHERS TRIMESTER III - Munawarah, Raudhatul; Ayu Pertiwi, Nur Fitri; Andreastuti, Hana (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Background: in Indonesia (2020), under-five mortality, 72.0% are neonates (age 0-28 days). One of the causes is the lack of colostrum giving, colostrum plays a role in protecting the baby's intestines and stomach from infection. Colostrum expenditure of pregnant women is influenced by one of them with breast care, many pregnant women do not pay attention to breast care according to SOPs so that colostrum expenditure is > 1 day after giving birth. Objective: The purpose of this study was to determine the effect of breast care on colostrum production in third trimester pregnant women at the Harapan Bunda Clinic. Research design: experimental posttest-only control design. The research technique used purposive sampling with each group of 15 respondents. The data collection technique used direct observation in January-February 2022. Results: data analysis using the Mann Whitney test obtained a significant value (p = 0.000). The majority of colostrum expenditure in the control group was > 1 day of delivery, while in the treatment group the majority of colostrum expenditure was before delivery. The results of the analysis showed that there was an effect of breast care on colostrum expenditure in third trimester pregnant women. Conclusion: There is an effect of breast care on the production of colostrum in third trimester pregnant women. The results of this study serve as input for the Harapan Bunda Clinic in order to improve education for pregnant women to carry out breast care.